(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Backgrounds: As there is no published data regarding the response to Anti-retroviral therapy (ART) among HIV patients from Bangladesh. The present study was designed to determine the immunological and virological responses of HIV infected Bangladeshi adults starting ART. Objectives: To monitor the changes of CD4 and CD8 T-lymphocyte count and Viral load (VL) before and after three and six months of starting ART. Methods: 20 symptomatic HIV infected patients with CD4 T-lymphocyte count of <350 cells/µ] of blood were initiated ART.CD4 and CDS T-lymphocyte counts were estimated by Flowcytometer and VL was dete1mined by real-time PCR technique. Results: The mean CD4 T-lymphocyte count among the sn1dy patients were 177±127 cells/µl before initiation of ART. After ART initiation, their mean CD4 count increased significantly to 368±181 and 452±183 cellshll after three and six months respectively (P<0.0001).The mean CDS T-lymphocyte counts were 901±650 cells/µ! before initiation of ART, which increased to I 085±393 and 1121±372 cells/µl after three and six months respectively after ART initiation (P>0.05). Before ART initiation, the mean VL was 5.25±1.19 log10 (copies/ml) among the study population which became undetectable in 15 (75%) patients after three months of ART and in another 2 (10%) patients after 6 months of ART initiation. Conclusion: Our study concluded that, ART is effective in slowing the progression of HIV infection to AIDS with good immunological and virological outcome among the ART initiators.